2015
DOI: 10.1093/ntr/ntv182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Electronic Cigarette Liquid Nicotine Concentration on Plasma Nicotine and Puff Topography in Tobacco Cigarette Smokers: A Preliminary Report

Abstract: Liquid nicotine concentration can influence plasma nicotine concentration in ECIG-naïve cigarette smokers, and, at some concentrations, the nicotine delivery profile of a 3.3V ECIG with a dual coil, 1.5-Ohm cartomizer approaches that of a combustible tobacco cigarette in this population. Finding a product that delivers nicotine as effectively as a tobacco cigarette, as we report here, may be essential for smokers who want to replace completely their combustible tobacco cigarettes with ECIGs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
112
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 13 publications
5
112
0
Order By: Relevance
“…8 E-cigarettes are available with a wide variety of nicotine concentrations, ranging from 0 mg/mL (i.e., no nicotine) to over 25 mg/mL, 9 and use of e-cigarettes with higher nicotine concentrations has been shown to increase nicotine delivery to the blood stream and enhance the rewarding effects of vaping. 10, 11 Accordingly, adolescents who use e-cigarettes with higher levels of nicotine may be at greater risk of developing a tolerance to and dependence on nicotine, which could contribute to both the persistence and progression of vaping as well as use of combustible tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…8 E-cigarettes are available with a wide variety of nicotine concentrations, ranging from 0 mg/mL (i.e., no nicotine) to over 25 mg/mL, 9 and use of e-cigarettes with higher nicotine concentrations has been shown to increase nicotine delivery to the blood stream and enhance the rewarding effects of vaping. 10, 11 Accordingly, adolescents who use e-cigarettes with higher levels of nicotine may be at greater risk of developing a tolerance to and dependence on nicotine, which could contribute to both the persistence and progression of vaping as well as use of combustible tobacco products.…”
Section: Introductionmentioning
confidence: 99%
“…Azzopardi et al 25 and Adamson et al 7,28 showed how deposited mass and nicotine quantification at the cellular exposure interface enable appropriate extrapolation and comparisons in an aerosol matrix. Different types of e-cigarettes and e-liquids generate different volumes of aerosol and deliver different amounts of nicotine, however typically smokers who switch from cigarette to nicotine delivery devices adapt their behavior to potentially titrate for nicotine 18,19 . With this being considered, Shen et al reported that primary airway cells exposed to whole e-cigarette aerosol generated at ISO smoking regimen had a lesser impact on differential gene expression than combustible cigarette 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, dose matching between combustible cigarette and e-cigarettes can be conducted based on deposited mass or puff numbers. This, however, does not account for the reported change in smoking behavior to titrate for serum nicotine when subjects switch products 18,19 . Therefore, a sensible approach would be to conduct comparative product assessment using an intense smoking regimen that delivers a similar nicotine dose range across the tested products.…”
mentioning
confidence: 93%
“…Nicotine uptake through e-cigarette use depends on the nicotine concentration (mg/ml) of the e-liquid being consumed, the design of the device, the user's puffing behavior, and the user's experience with the product [31][32][33][34]. This section of the report speculates that highperformance e-cigarettes may promote higher absorption of nicotine than tobacco cigarettes.…”
Section: Effects Of Nicotine Inhalation By the E-cigarette Usermentioning
confidence: 99%